Heterogeneity, High Performance Computing, Self-Organization and the Cloud - Lynn, Theo; Morrison, John P.; Kenny, David (Palgrave Studies in Digital Business & Enabling Technologies, 2018)
application; blueprints; self-management; self-organisation; resource management; supply chain; big data; PaaS; Saas; HPCaaS